Strategi Pengembangan Merek Pada Sawah Lope di Desa Cikaso Kuningan - Donant Alananto Iskandar; Joseph M.J Renwarin; Anandra Isjiwo; Anna Maria Godeliva; F.X. Jordi Hanzdima; Ifdlal Muhammad Amir; . et.al. (LPMP Imperium, 2023)
This article discusses the importance of a brand to the attractiveness of a product, both goods and services. The tourist business is also one of them, without good branding it is difficult to attract the attention of tourists to visit. Kuningan is one of the areas in Indonesia which actually has a lot of tourism potential. Even though in Kuningan there are lots of tourist destinations, both local and foreign tourists rarely know about tourist attractions, especially tourist villages in Kuningan. Sawah Lope is one of them, Sawah Lope, which is located in the village of Cikaso Kuningan, has many beautiful tourist attractions and natural resources that are rarely visited by tourists. This can happen because the residents there and the local government are not able to carry out promotions and market their area so that they can be attracted by tourists, from local to foreign tourists.